A dynamic theory of collateral quality and long-term interventions - Michael Junho Lee; Daniel Neuhann (Federal Reserve Bank of New York, 2019)
We study a dynamic model of collateralized lending under adverse selection in which the quality of collateral assets is endogenously determined by hidden effort. Complementarities in incentives lead to non-ergodic dynamics: Asset quality and output grow when asset quality is high, but stagnate or deteriorate otherwise. Inefficiencies remain, even in the most efficient competitive equilibrium-investment and output are vulnerable to spells of lending market illiquidity, and these spells may persist because of suboptimal effort. Nevertheless, benevolent regulators without commitment can destroy welfare by prioritizing liquidity over incentives. Optimal interventions with commitment call for large, long-term subsidies in excess of what is required to restore liquidity.
Keywords: E44; E50; G01; G18; 330; liquidity; government intervention; adverse selection; collateral